Perspektif Preferensi Konsumen Remaja terhadap Jajanan Tradisional Khas Gresik - Asparin, Arinda; Sudiyarto, Sudiyarto (Department of Agribusiness, Halu Oleo University, 2021)
This study aims to explain the order of attributes of Gresik's traditional snacks based on the level of importance according to adolescent consumer preferences and the combination of Gresik's traditional snack product attribute levels, which are adolescent consumers' preferences Gresik Regency. The method used in determining the sample is purposive sampling. The respondents used were 55 teenagers who had made purchases and consumed snacks at least once. Location selection technique using the purposive method. This research was conducted from March 2021 to June 2021. Methods of data collection using closed questionnaires and case studies. The research data were analyzed using conjoint analysis with a combination of 7 attributes. Based on the study results, the order of attributes of Gresik's traditional snacks based on the level of importance according to adolescent consumer preferences was taste, brand, elasticity, price, product appearance, aroma, and packaging materials. The combination of the attribute levels of Gresik's traditional snacks that are the preferences of adolescent consumers in Gresik Regency is sweet to taste, very famous brand, sufficient elasticity, low price, attractive colour, medium characteristic aroma, and paper packaging material.